Digital study of the ¹⁴N(γ,2α)⁶Li reaction - Afanasiev, S.N.; Afanasieva, I.O. (Problems of Atomic Science and Technology, 2023)
A digital measurement technique of points coordinates along the tracks was developed for the stereo frame photonuclear reaction data bank created in KIPT. The main procedure is the analysis of pixel intensity in the area of tracks. The ¹⁴N(γ,2α)⁶Li reaction was chosen as a test reaction for measurement. A kinematic scheme for calculating the physical parameters of the reaction was created assuming a two-particle decay mode with the formation of an intermediate excited state. Experimental data and kinematic calculation were compared. Для створеного в ННЦ ХФТІ банку даних стереокадрів фотоядерних реакцій розроблено методику цифрового вимірювання координат точок уздовж треків. Основною процедурою є аналіз інтенсивності пікселів у області треків. Як тестову для вимірювання обрано реакцію ¹⁴N(γ,2α)⁶Li. Створено кінематичну схему розрахунку фізичних параметрів реакції в припущенні двочастинкової моди розпаду з утворенням проміжного збудженого стану. Виконано порівняння експериментальних даних і кінематичного розрахунку.